Incidence of adverse drug reactions in human immune deficiency virus-positive patients using highly active antiretroviral therapy - B Akshaya Srikanth; S Chandra Babu; Harlokesh Narayan Yadav; Sunil Kumar Jain (Wolters Kluwer Medknow Publications, 2012)
To estimate the incidence of adverse drug reactions (ADRs) in Human immune deficiency virus (HIV) patients on highly active antiretroviral therapy (HAART). To identify the risk factors associated with ADRs in HIV patients. To analyze reported ADRs based on various parameters like causality, severity, predictability, and preventability. Retrospective case-control study. An 18-month retrospective case-control study of 208 patients newly registered in ART center, RIMS hospital, Kadapa, were intensively monitored for ADRs to HAART. Predictability was calculated based on the history of previous exposure to drug. Multivariate logistic regressions were used to identify the risk factors for ADRs. Data were analyzed using the chi-square test for estimating the correlation between ADRs and different variables. All statistical calculations were performed using EpiInfo version 3.5.3. Monitoring of 208 retrospective patients by active Pharmacovigilance identified 105 ADRs that were identified in 71 patients. Skin rash and anemia were the most commonly observed ADRs. The organ system commonly affected by ADR was skin and appendages (31.57%). The ADRs that were moderate were 90.14% of cases. The incidence of ADRs (53.52%) was higher with Zidovudine + Lamivudine + Nevirapine combination. CD4 cell count less than <250 cells/μl were 80.28%, male gender were observed to be the risk factors for ADRs. Our study finding showed that there is a need of active pharmaceutical care with intensive monitoring for ADRs in Indian HIV-positive patients who are illiterate, of male and female gender, with CD4 count ≤250 cells/mm 3 with comorbid conditions.